2012
DOI: 10.1182/blood-2012-02-413161
|View full text |Cite
|
Sign up to set email alerts
|

Activity of pomalidomide in patients with immunoglobulin light-chain amyloidosis

Abstract: Immunoglobulin light-chain (AL) amyloidosis is a rare, incurable plasma cell disorder. Its therapy has benefited immensely from the expanding drug armamentarium available for multiple myeloma. Pomalidomide in combination with weekly dexamethasone (Pom/dex) is active among patients with relapsed myeloma. In the present study, we explored the Pom/dex combination in patients with previously treated AL. Patients were eligible for this prospective phase 2 trial if they had had at least one prior regimen and if they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 136 publications
(80 citation statements)
references
References 31 publications
5
74
0
1
Order By: Relevance
“…15 Frequently, these responses are of limited duration (14.1-month median progression-free survival in the pomalidomide study and not yet reported in those receiving carfilzomib) and therapeutic options for relapsed patients remain limited.…”
Section: Resultsmentioning
confidence: 99%
“…15 Frequently, these responses are of limited duration (14.1-month median progression-free survival in the pomalidomide study and not yet reported in those receiving carfilzomib) and therapeutic options for relapsed patients remain limited.…”
Section: Resultsmentioning
confidence: 99%
“…Although pomalidomide/dexamethasone has already been shown to have activity in AL amyloidosis by Dispenzieri et al, 14 our trial is different in that it includes a dose-escalation format to arrive at an MTD. This study design was prompted by the experience of lenalidomide dosing in AL amyloidosis.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Two independent trials showed efficacy of pomalidomide in AL amyloidosis; hematologic response occurred in 48% to 50% of patients. 9,10 However, these studies could not show an impact of response on survival. We designed the present phase 2 trial to assess the efficacy, safety, and impact on survival of the combination of pomalidomide and dexamethasone (PDex) in patients with AL amyloidosis treated upfront with bortezomib and an alkylating agent.…”
Section: Introductionmentioning
confidence: 89%